Estudo comparativo dos métodos de dessulfurização do biogás - Frascá, Glaucia de Natali (Universidade Federal de São Carlos, 2023)
Biogas represents one of the most promising sources of renewable energy today, emerging as a sustainable alternative to fossil fuels and contributing to overcome the challenges associated with climate change. Derived from the anaerobic decomposition of organic matter, biogas is composed mainly of methane and carbon dioxide, in addition to other components in smaller proportions, such as hydrogen sulfide (H2 S). The H2S, even being present in low concentrations, is highly harmful for the various purposes that biogas may have. Not only does it reduce its calorific value, it is also corrosive to storage and distribution systems. Thus, it is necessary that the H2 S is efficiently removed from the biogas. This work provides an overview of which techniques to remove H2S from Biogas have been gaining prominence in recent decades and which challenges still need to be overcome. Since adsorption, one of the most traditional methods, is still one of the most studied strategies, with emphasis on the constant search for effective adsorbents that contribute to a reduction in the cost normally linked to this process. In this sense, the combination of proven effective adsorbents with different compounds (such as Fe, Zn, NaOH, KOH, among others) can promote greater interactions with H2S molecules, making these options promising. Another option, biological processes such as biofilters have attracted great attention in recent years. These methods use microbial cultures to convert H2S into less harmful compounds and present encouraging results, promoting significant removals of H2S, in addition to economic and environmental advantages, since they can use by-products from other industries and, unlike adsorption, do not generate large volumes of waste.
Comparative study of biogas desulfurization methods
Keywords: Remoção H2S biogás; Dessulfurização biogás; Adsorção biogás; Biofiltração; ENGENHARIAS::ENGENHARIA QUIMICA